The Effect of Two Stay Two Stray Models on Social Studies Learning Outcomes of Grade 5 Elementary School Students - Latifatul Zurroh (Universitas Muhammadiyah Sidoarjo, 2018)
The purpose of this research is whether there is influence or not on the application of Two Stay Two Stray model on fifth grade student’s social science learning performence in AL-ISLAH Elementery school. The method applied by this research was quantative experiment. The design of thes research takes the fifth grade students of AL-ISLAH Elementery school as the populatin and 30 of the total as the sample. The data collecting technique uses test. Meanwhile, the analysis of the data runs hypotheses test and Eta Squared formula. The result of the application of Two Stay Two Stray model on fifth grade student’s social science learning performence in AL-ISLAH Elementery school.showed that t-account is more than t-table. It is 22,20>1,699. The acquared data shows if the application of Two Stay Two Stray learning model has influence on fifth grade student’s social science learning performence in AL-ISLAH Elementery school. By Eta Squared, it shows 0,94>0,14. Based on the data by Eta Squared indicates that the influence given is moderately big towards student’s learning performance.